Love across borders : Asian Americans, race, and the politics of intermarriage and family-making - Chong, Kelly H., 1964- (New York, NY : Routledge, 2021)
"Love Across Borders explores intermarriage and family-making to explore the meaning of racial boundary-crossing unions for Asian Americans. Based on extensive data, the book sheds light on the experiences, social positions, and racial incorporation of persons of Asian-descent. One of the fastest growing U.S. minorities, Asian Americans are an 'in-between' group ambiguously situated in a society dominated by a black-white racial divide. Asian Americans are now increasingly diverse in terms of countries of origin, class status, and religion. This study of Asian American intermarriage reveals much about the historical and changing experiences of Asian Americans, their racial/ethnic identity formation, their incorporation into the American society, and the larger politics of race, gender, and immigration. This book foregrounds the issues of race and racialized desires among Asian Americans, interrogating the impact of the globally circulating racial discourses and other types of hegemonic cultural narratives emanating from the West that influence the subjectivities and choices of Asian Americans. At the same time, it explores how they are able to navigate and challenge these discourses and structures of inequality within the context of intermarriage and cultural/identity struggles."--Provided by publisher.
OCLC-licensed vendor bibliographic record.
Keywords: Intermarriage -- United States -- 21st century; Asian Americans -- Race identity -- History -- 21st century; Racially mixed families -- United States -- History; SOCIAL SCIENCE / Sociology / General